The Quran and Restoration of Education - Setiawan, Andry; Suhartini, Andewi (PT. Riset Press International, 2024)
This paper explores pedagogical approaches to teaching Al-Qur'an in Islamic schools. It examines various methods and strategies employed by educators to effectively impart the teachings of Al-Qur'an to students within the context of Islamic education. The study delves into the importance of integrating Al-Qur'an into the curriculum and discusses the challenges and opportunities associated with teaching Al-Qur'an in Islamic schools. Additionally, it highlights the role of teachers in implementing pedagogical approaches that engage students and foster a deeper understanding and appreciation of Al-Qur'an. The findings of this paper contribute to the ongoing discourse on enhancing the quality of Islamic education through innovative pedagogical.